Fresh evidence on the influence of trading activities on CO2 emissions in developed and developing high CO2 emitting countries: long panel data modelling - Muhammad Jawad, Iqbal; Abdul Rahim, A.S.; Ng, Shing Leng; Sulaiman, Chindo; Samad, Nur Syafiqah A. (Inderscience, 2023)
There is a widespread concern for environmental quality across the world due to greenhouse gases especially carbon dioxide (CO2) emission, which is the main source of global warming. Both trade and carbon dioxide emissions are rising simultaneously over the years. This paper investigates the relationship between trade openness and carbon dioxide emissions in developed and developing high CO2 emitting countries over the 1971-2017 period. Panel cointegration and pooled mean group (PMG) techniques were employed. The PMG result revealed that trade openness is positively related to CO2 emission for the top emitters from developing countries and hence causes environmental degradation in the long-run. However, trade is negatively related to carbon dioxide emission for the top emitters from developed countries where trade liberalisation appears to increase environmental quality. These findings deliver insights on the need to protect the environment from degradation by adopting green technologies that are environmentally friendly with high-energy efficiency.